(3RS)-S-[1-(3-Chlorophenyl)-2-oxopyrrolidin-3-yl]-N,N '-dimethylthiouronium bromide - Drabina, Pavel; Hanusek, Jiří; Sedlák, Miloš; Růžička, Aleš (International Union of Crystallography, 2009)
The title molecule, C13H17ClN3OS+·Br-, consists of benzene and pyrrolidine rings and an S-C(NHCH3)2 group. The central C-N bond lengths in the S-C(NHCH3)2 fragment indicate partial double-bond character. Molecules are interconnected into chains by N-H...Br hydrogen bonds and the chains are linked into pairs by weak C-H...Br hydrogen bonds.
Keywords: single-crystal X-ray study; T = 150 K; mean (C–C) = 0.006 A°; R factor = 0.048; wR factor = 0.114; data-to-parameter ratio = 18.3